Fabrication of 3D concentric amphiphilic microparticles to form uniform nanoliter reaction volumes for amplified affinity assays. Issue 19 (8th September 2020) - Destgeer, Ghulam; Ouyang, Mengxing; Wu, Chueh-Yu; Di Carlo, Dino
Abstract : Uniform fluid compartments are formed inside shape-coded amphiphilic particles using simple fluid exchange steps. This lab on a particle system enables multiplexed enzymatic reactions without cross talk to democratize cutting-edge biological assays. Abstract : Reactions performed in uniform microscale volumes have enabled numerous applications in the analysis of rare entities ( e.g. cells and molecules). Here, highly monodisperse aqueous droplets are formed by simply mixing microscale multi-material particles, consisting of concentric hydrophobic outer and hydrophilic inner layers, with oil and water. The particles are manufactured in batch using a 3D printed device to co-flow four concentric streams of polymer precursors which are polymerized with UV light. The cross-sectional shapes of the particles are altered by microfluidic nozzle design in the 3D printed device. Once a particle encapsulates an aqueous volume, each "dropicle" provides uniform compartmentalization and customizable shape-coding for each sample volume to enable multiplexing of uniform reactions in a scalable manner. We implement an enzymatically-amplified immunoassay using the dropicle system, yielding a detection limit of <1 pM with a dynamic range of at least 3 orders of magnitude. Multiplexing using two types of shape-coded particles was demonstrated without cross talk, laying a foundation for democratized single-entity assays.